AKTIVITAS BELAJAR ANAK SELAMA MASA BELAJAR DARI RUMAH DI DESA MEKO - I Komang Mertayasa (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2020)
The availability of internet access by junior high school level children in Meko Village has been used to access youTube, Facebook, WhatsApp, Massenger, Twitter, Line and only a few of them use it to add references in completing assignments given by the teacher. Ownership of gadgets and Personal Computers (PC) which are limited to children from economically established families and existing internet networks have not been used to conduct online learning with accessing websites prepared by the Ministry of Education and Culture. Learning activity is done offline by giving assignments that can provide meaningful learning experiences through learning activities undertaken by children while Learning From Home. Activities undertaken by junior high school-level children during the Learning From Home in Meko Village are reading religious books, conduct discussions online, make a summary and searching for online material.